Analysis of students' basic basketball skills: A comparative study of male and female students - HaÃ¯dara, Youssouf; Okilanda, Ardo; Dewintha, Rezza; Suryadi, Didi (Universitas Tanjungpura, 2023)
This study aims to prove the difference in the ability of basic basketball techniques of grade I elementary school students between boys and girls. This research is descriptive quantitative with survey method, where in this research there are tests and measurements. The population in this study were all grade 1 students of SDN 10 Anjungan. The sampling technique used qouta sampling so that a sample of 32 students was obtained. The instruments in this study are dribbling using zig-zag, passing using chest pass technique, shooting by shooting free throw, lay-up by doing step running and jumping with two feet. Data analysis using the SPSS application. The results showed a significance value of 0.643> 0.05 so there was no significant difference. The conclusion is that there is no significant difference in the ability of basic basketball techniques between male students and female students.